Identification key for fishes from coastal streams of the Atlantic forest of southeastern Brazil - Goncalves, Cristina da Silva [UNESP]; Carvalho, Fernando Rogerio; Perez-Mayorga, Maria Angelica [UNESP]; Oliveira, Isadora Francesconi de [UNESP] (Revista Biota Neotropica, 2017)
In recent decades, current knowledge about fish from Neotropical streams has greatly increased, but is still deficient. Here we present an identification key for fishes from coastal freshwater streams from a large conservation area of Atlantic rainforest of southeastern Brazil, including 39 species. Considering that most of these species (61.2%) are endemic to the coastal streams, this identification key will be useful not only for the species recognition of the sampled area, but also for the surrounding coastal region.
Keywords: taxonomy; endemic and endangered fishes; Neotropical streams; Jureia-Itatins Ecological Station